Adrenal fatigue does not exist. A systematic review of the medical literature - Cadegiani, Flavio Adsuara [UNIFESP] (2016)
Background: The term “adrenal fatigue” (“AF”) has been used by some doctors, healthcare providers, and the general media to describe an alleged condition caused by chronic exposure to stressful situations. Despite this, “AF” has not been recognized by any Endocrinology society, who claim there is no hard evidence for the existence. The aim of this systematic review is to verify whether there is substantiation for “AF”. Methods: A systematic search was performed at PUBMED, MEDLINE (Ebsco) and Cochrane databases, from the beginning of the data until April 22nd, 2016. Searched key words were: “adrenal” + “fatigue”, “adrenal” + “burnout”, “adrenal” + “exhaustion”, “hypoadrenia”, “burnout” + “cortisol”, “fatigue” + “cortisol”, “clinical” + “burnout”, “cortisol” + “vitalility”, “adrenal” + “vitality”, and “cortisol” + “exhaustion”. Eligibility criteria were: (1) articles written in English, (2) cortisol profile and fatigue or energy status as the primary outcome, (3) performed tests for evaluating the adrenal axis, (4) absence of influence of corticosteroid therapy, and (5) absence of confounding diseases. Type of questionnaire to distinct fatigued subjects, population studied, tests performed of selected studies were analyzed. Results: From 3,470 articles found, 58 studies fulfilled the criteria: 33 were carried in healthy individuals, and 25 in symptomatic patients. The most assessed exams were “Direct Awakening Cortisol” (n=29), “Cortisol Awakening Response” (n=27) and “Salivary Cortisol Rhythm” (n=26). Discussion: We found an almost systematic finding of conflicting results derived from most of the studies methods utilized, regardless of the validation and the quality of performed tests. Some limitations of the review include: (1) heterogeneity of the study design; (2) the descriptive nature of most studies; (3) the poor quality assessment of fatigue; (4) the use of an unsubstantiated methodology in terms of cortisol assessment (not endorsed by endocrinologists); (5) false premises leading to an incorrect sequence of research direction; and, (6) inappropriate/invalid conclusions regarding causality and association between different information. Conclusion: This systematic review proves that there is no substantiation that “adrenal fatigue” is an actual medical condition. Therefore, adrenal fatigue is still a myth.